EFFECT OF SILICA FUME SUBSITITUTION IN CEMENT AND ADDITION OF POLYPROPYLENE FIBER - resti nur arini; Farhan Rizky Yulihendrika; Fadli Kurnia; Ramadhani Isna (Jurnal Infrastruktur, 2023)
To fulfill the needs of construction materials both structural and non-structural in concrete, concrete forming materials are needed that have good resistance to the environment and can also improve the mechanical properties of concrete. One of the materials that can help improve the mechanical properties of concrete is by adding polypropylene fiber and silica fume to the mixture. The addition of silica fume as a substitute for cement is one of the alternatives used to utilize waste so as to reduce the use of cement. besides adding silica fume, the addition of polypropylene fiber can also affect physical properties because one of the advantages of using polypropylene fiber can reduce cracking at a young age. So by adding polypropylene fiber and silica fume into the mixture is expected to increase the compressive strength. In this research, we will substitute silica fume for cement and add polypropylene fibers to the concrete mix. The percentage of silica fume used for cement substitution is 2%, 4%, 6% and 8% while for fiber addition is 1% and 0.5%. From the results of silica fume substitution and the addition of polypropylene fiber, the maximum compressive strength value of the mortar will be sought. From the results of the compressive strength test, the addition of 0.5% polypropylene fiber and the addition of 8% silica fume produced the highest compressive strength, which is around 6.02 MPA.